2014
DOI: 10.1089/dna.2014.2577
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Effect of rs688 and rs5925 in Regulating Low-Density Lipoprotein Receptor Splicing

Abstract: Analysis of the low-density lipoprotein receptor (LDLR) gene based on the rs688 and rs5925 genetic polymorphisms has provided evidence suggesting that haplotypes related to rs688 and rs5925 are associated with ischemic cerebrovascular diseases. Both rs688 and rs5925 have been empirically identified as exon-splicing enhancers in silico, and rs688 has been shown to be a functional polymorphism that modulates LDLR exon 12 splicing efficiency both in vitro and in vivo. The aim of this study was to evaluate whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…It was indicated that the GA genotype of the rs5925 polymorphism is associated with decreased susceptibility to CAD with an OR = 0.45 (95% CI, 0.27–0.75), RR = 0.65 (0.47–0.88), P = 0.002. The rs5925 polymorphism (in cooperation with the rs688 polymorphism) has been shown to regulate the splicing efficiency of the LDLR gene [29]. This result may be consistent with a study that showed that the rs5925 polymorphism is associated with the thickness of the carotid-intima media in Slovenian type 2 diabetes T2D patients [30].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It was indicated that the GA genotype of the rs5925 polymorphism is associated with decreased susceptibility to CAD with an OR = 0.45 (95% CI, 0.27–0.75), RR = 0.65 (0.47–0.88), P = 0.002. The rs5925 polymorphism (in cooperation with the rs688 polymorphism) has been shown to regulate the splicing efficiency of the LDLR gene [29]. This result may be consistent with a study that showed that the rs5925 polymorphism is associated with the thickness of the carotid-intima media in Slovenian type 2 diabetes T2D patients [30].…”
Section: Discussionsupporting
confidence: 83%
“…We suggest that the T allele of the rs1529729 polymorphism and the GA genotype of the rs5925 polymorphism protect against CAD by increasing the expression of LDLR at the hepatocyte surface such that LDL-C uptake and metabolism is enhanced. In support of this suggestion, the rs5925 polymorphism has been described as an exon-splicing enhancer [29]. However, the effect of rs1529729 and rs5925 polymorphisms on LDLR expression should be to be elucidated in a future study.…”
Section: Discussionmentioning
confidence: 91%
“…This polymorphism variation is sufficient to explain the differences of LDLR involving exon 13 in splicing efficiency. The C allele can result in enhanced exon 13 splicing efficacy in LDLR [38]. Therefore, the effects LDLR rs5925 observed in the present study on the prevalence of PTSD and plasma lipid profiles in the male and female subjects with or without PTSD may be due to the difference of splicing efficiency.…”
Section: Discussionmentioning
confidence: 56%
“…Tratándose de cambios en el intrón (rs885765) o en regiones no traducidas del gen (rs55903358 y rs5742911), es posible que su papel sea regulador; por su parte, los cambios dentro de los exones (rs688 y rs5925) son sinónimos; sin embargo, hay estudios que revelan su influencia sobre la modulación del proceso de corte y empalme del gen, produciendo diferencias en los niveles del colesterol LDL (54,55).…”
Section: Discussionunclassified